Frontispiece: Bioinspired copper single‐atom nanozyme as a superoxide dismutase‐like antioxidant for sepsis treatment (EXP2 4/2022). Issue 4 (31st August 2022) - Yang, Ji; Zhang, Ruofei; Zhao, Hanqing; Qi, Haifeng; Li, Jingyun; Li, Jian‐Feng; Zhou, Xinyao; Wang, Aiqin; Fan, Kelong; Yan, Xiyun; Zhang, Tao
Abstract : A SOD‐inspired copper single‐atom nanozyme (Cu‐SANzyme) was designed and synthesized by a two‐step scaffoldadsorption method. The Cu‐SANzyme exhibits high catalytic activity to scavenge superoxide anion, the initiator of ROS, and thus effectively prevents the disease progression in septic animals.